A simulation study of left ventricular decompression using a double lumen arterial cannula prototype during a veno-arterial extracorporeal membrane oxygenation - Ježek, Filip; Strunina, Svitlana; Carlson, Brian E; Hozman, Jiří (The International journal of artificial organs, 2019)
BACKGROUND: Veno-arterial extracorporeal membrane oxygenation can be vital to support patients in severe or rapidly progressing cardiogenic shock. In cases of left ventricular distension, left ventricular decompression during veno-arterial extracorporeal membrane oxygenation may be a crucial factor influencing the patient outcome. Application of a double lumen arterial cannula for a left ventricular unloading is an alternative, straightforward method for left ventricular decompression during extracorporeal membrane oxygenation in a veno-arterial configuration. OBJECTIVES: The purpose of this article is to use a mathematical model of the human adult cardiovascular system to analyze the left ventricular function of a patient in cardiogenic shock supported by veno-arterial extracorporeal membrane oxygenation with and without the application of left ventricular unloading using a novel double lumen arterial cannula. METHODS: A lumped model of cardiovascular system hydraulics has been coupled with models of non-pulsatile veno-arterial extracorporeal membrane oxygenation, a standard venous cannula, and a drainage lumen of a double lumen arterial cannula. Cardiogenic shock has been induced by decreasing left ventricular contractility to 10% of baseline normal value. RESULTS: The simulation results indicate that applying double lumen arterial cannula during veno-arterial extracorporeal membrane oxygenation is associated with reduction of left ventricular end-systolic volume, end-diastolic volume, end-systolic pressure, and end-diastolic pressure. CONCLUSIONS: A double lumen arterial cannula is a viable alternative less invasive method for left ventricular decompression during veno-arterial extracorporeal membrane oxygenation. However, to allow for satisfactory extracorporeal membrane oxygenation flow, the cannula design has to be revisited.
Keywords: katetrizace centrálních vén; Decompression, Surgical; Reproducibility of Results; Ventricular Dysfunction, Left; dysfunkce levé srdeční komory; Catheterization, Central Venous; kanyla; design vybavení; reprodukovatelnost výsledků; Computer Simulation; mimotělní membránová oxygenace; počítačová simulace; circulation; srdeční komory; Adult; Equipment Design; Catheterization; chirurgická dekomprese; Shock, Cardiogenic; Humans; Extracorporeal Membrane Oxygenation; double lumen cannula; Heart Ventricles; Extracorporeal membrane oxygenation; model; kardiogenní šok; Cannula; modelica; dospělí; katetrizace; cannula; lidé